Venomous snakes of Costa Rica: biological and medical implications of their venom proteomic profiles analyzed through the strategy of snake venomics - Lomonte, Bruno (2014)
artículo (arbitrado)-- Universidad de Costa Rica, Instituto de Investigación Clodomiro Picado, 2014. Este documento es privado debido a limitaciones de derechos de autor.